2013
DOI: 10.1103/physreva.87.053617
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of phase transitions and hysteresis near the onset of Bose-Einstein condensation

Abstract: Multiple phases occurring in a Bose gas with finite-range interaction are investigated. In the vicinity of the onset of Bose-Einstein condensation (BEC) the chemical potential and the pressure show a van-der-Waals like behavior indicating a first-order phase transition although there is no longrange attraction. Furthermore the equation of state becomes multivalued near the BEC transition. For a Hartree-Fock or Popov (Hartree-Fock-Bogoliubov) approximation such a multivalued region can be avoided by the Maxwell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…It is well known that mean-field approaches, such as the Popov theory and the HF theory, usually lead to a BEC transition of first order. The normal-superfluid PS was also predicted for spinless bosons with purely repulsive interactions [34][35][36], in which case the false spinodal decomposition near the BEC transition is due to the unphysical multi-valued behavior of the mean-field EoS. Such artifact differs from the results presented here, where the mechanical instability is caused by the interspin attraction.…”
contrasting
confidence: 41%
“…It is well known that mean-field approaches, such as the Popov theory and the HF theory, usually lead to a BEC transition of first order. The normal-superfluid PS was also predicted for spinless bosons with purely repulsive interactions [34][35][36], in which case the false spinodal decomposition near the BEC transition is due to the unphysical multi-valued behavior of the mean-field EoS. Such artifact differs from the results presented here, where the mechanical instability is caused by the interspin attraction.…”
contrasting
confidence: 41%
“…It is a consequence of the hierarchical dependencies of correlations [80]. This scheme of multiple-scattering corrected T -matrix has been successfully applied to describe the critical behaviour in and outside a condensate in superconductivity [81] and in Bose-Einstein condensation [82,83].…”
Section: Multiple-scattering Corrected T -Matrix Approachmentioning
confidence: 99%
“…Recently it has been shown that one can arrive at the same equations by a completely conserving theory of multiple corrected T‐matrix [ 56–58 ] with equivalent results. [ 59,60 ] This illustrates that the anomalous propagators are a theoretical shortcut to the right result through adopting inconsistent propagators.…”
Section: Introductionmentioning
confidence: 99%